Extragalactic science with the experiment for cryogenic large-aperture intensity mapping. Issue 4 (25th March 2023) - Pullen, Anthony R; Breysse, Patrick C; Oxholm, Trevor; Switzer, Eric R; Anderson, Christopher J; Barrentine, Emily; Bolatto, Alberto D; Cataldo, Giuseppe; Essinger-Hileman, Thomas; Maniyar, Abhishek S; Stevenson, Thomas; Somerville, Rachel S; et al.
ABSTRACT: The EXperiment for Cryogenic Large-Aperture Intensity Mapping (EXCLAIM) is a balloon-borne cryogenic telescope that will survey the spectrum of diffuse emission from both the Milky Way and the cosmic web to probe star formation, the interstellar medium, and galaxy evolution across cosmic time. EXCLAIM's primary extragalactic science survey maps 305 deg 2 along the celestial equator with an R = 512 spectrometer over the frequency range ν = 420 − 540 GHz, targeting emission of the [C ii ] line over redshifts 2.5 < z < 3.5 and several CO lines for z < 1. Cross-correlation with galaxy redshift catalogues isolates line emission from the large-scale structure at target redshifts. In this paper, we forecast the sensitivity for both the two-point and conditional one-point cross-correlation. We predict that EXCLAIM will detect both the [C ii ]-QSO cross-power spectrum and the conditional voxel intensity distribution (CVID) at various redshifts under a broad range of [C ii ] intensity models, allowing it to differentiate among these models in the literature. These forecasts for the power spectra include the effects of line interlopers and continuum foreground contamination. We then convert the joint [C ii ] constraints from both the cross-power spectrum and the CVID into constraints on the [C ii ] halo luminosity–mass relation L_[C II](M) model parameters and the star formation rate density (SFRD) from [C ii ] emission. We also develop sensitivity estimates for CO, showing the ability to differentiate between models.